2012
DOI: 10.1111/jce.12032
|View full text |Cite
|
Sign up to set email alerts
|

High Density Mapping of Atrial Fibrillation During Vagal Nerve Stimulation in the Canine Heart: Restudying the Moe Hypothesis

Abstract: In contrast to the prediction of the multiple wavelet hypothesis, during AF in the Moe model, multiple foci drove the atria, producing and maintaining AF. Reentry played little, if any, role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 20 publications
2
38
0
1
Order By: Relevance
“…2,13,19 The study by de Groot et al 2 postulates transmural conduction of fibrillation waves as the leading mechanism of epicardial breakthrough, whereas many others use radial spread of activation as criterion to identify ectopic focal discharges during AF. [20][21][22][23][24] Using radial spread of activation and QS electrogram morphology as criterion for ectopy, Lee et al 25 recently demonstrate that AF in dogs undergoing vagal stimulation can be maintained by multiple ectopic foci.…”
Section: Discussionmentioning
confidence: 99%
“…2,13,19 The study by de Groot et al 2 postulates transmural conduction of fibrillation waves as the leading mechanism of epicardial breakthrough, whereas many others use radial spread of activation as criterion to identify ectopic focal discharges during AF. [20][21][22][23][24] Using radial spread of activation and QS electrogram morphology as criterion for ectopy, Lee et al 25 recently demonstrate that AF in dogs undergoing vagal stimulation can be maintained by multiple ectopic foci.…”
Section: Discussionmentioning
confidence: 99%
“…24 A single relatively stable source in canine RA using a high concentration of acetylcholine by Schuessler et al, 8 and multifocal AF in the sterile pericarditis model by Waldo and colleagues, 6,25 as well, have been reported. Jalife and colleagues 4,26 used phase-based optical signal processing to demonstrate rotor activities with a spectrum of scenarios from single meandering rotor to multiple, periodic rotors giving rise to fibrillatory activation.…”
Section: Progressive Remodeling Of Atrial Tissue With Af Continuationmentioning
confidence: 99%
“…1,2 Multiple atrial wavelets, macroreentries, and localized (focal or reentrant) sources have been reported to contribute to the substrate of persistent AF. [3][4][5][6] For determining a therapeutic strategy in persistent AF (localized target versus global intervention), the key question is whether the multitude of activation waves that characterize persistent AF individually emanate from few, stable, periodic drivers or whether the waves are transitory, widely distributed, and self-perpetuating. Localized drivers are difficult to detect in persistent AF with conventional techniques because of sequential temporospatial mapping, lack of specificity of complex atrial electrograms, intermittent firing, and spatial meandering.…”
mentioning
confidence: 99%
“…Both experimental and human studies suggest rotor and ectopic activity to drive persistent AF. [7][8][9][10] However, detailed highdensity direct contact mapping studies in goat and humans identified multiple wavelets, increasing longitudinal dissociation and transmural conduction (epicardial breakthrough) as dominant AF mechanisms. [1][2][3][4][5] In these studies, stable rotors were rare and not sustained, and breakthroughs were largely because of transmural conduction rather than ectopic activity.…”
Section: Putative Af Mechanisms and Atrial Anatomymentioning
confidence: 99%